Regional issues in a global context rural change in Nova Scotia - Macintosh, Pamela J. (Truro , Nova Scotia, Canada Department of Humanities, Nova Scotia Agricultural College/Rural Research Centre, 1995)
The underlying theme of this paper is that rural communities must shift their economic, cultural and political orientations away from global competitiveness. Instead, they need to concentrate on local needs with a focus on community-based programs, ones initiated and supported by community members. We can't compete "sustainably" globally if local needs and wants are not secure.
Research Report No. 4
Keywords: Rural communities--Regional issues